2005
DOI: 10.1126/science.1105820
|View full text |Cite
|
Sign up to set email alerts
|

Al Cluster Superatoms as Halogens in Polyhalides and as Alkaline Earths in Iodide Salts

Abstract: Two classes of gas-phase aluminum-iodine clusters have been identified whose stability and reactivity can be understood in terms of the spherical shell jellium model. Experimental reactivity studies show that the Al13I-x clusters exhibit pronounced stability for even numbers of I atoms. Theoretical investigations reveal that the enhanced stability is associated with complementary pairs of I atoms occupying the on-top sites on the opposing Al atoms of the Al13- core. We also report the existence of another seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
332
0
10

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 437 publications
(352 citation statements)
references
References 34 publications
10
332
0
10
Order By: Relevance
“…8 For example, Castleman et al showed that metal clusters, such as Al 13 , could behave as superatoms, with reactivity resembling halide or alkali atoms. [9][10][11] However, the smaller peaks in the experimental spectra of sodium clusters, e.g., N = 10, 12, 14, and 26 cannot all be understood in the framework of strictly spherical Jellium model, 1 where the cluster is far from spherical. To explain the smaller peaks, Clemenger 12 suggested an ellipsoidal shell model, of which stability of the smaller peaks can be explained at 0.04 < U < 0.08.…”
mentioning
confidence: 99%
“…8 For example, Castleman et al showed that metal clusters, such as Al 13 , could behave as superatoms, with reactivity resembling halide or alkali atoms. [9][10][11] However, the smaller peaks in the experimental spectra of sodium clusters, e.g., N = 10, 12, 14, and 26 cannot all be understood in the framework of strictly spherical Jellium model, 1 where the cluster is far from spherical. To explain the smaller peaks, Clemenger 12 suggested an ellipsoidal shell model, of which stability of the smaller peaks can be explained at 0.04 < U < 0.08.…”
mentioning
confidence: 99%
“…3). Significantly, the growth of an analogous halide series was found to follow trends associated with polyfluorides and to develop by a unique chemistry after the formation of active sites on the cluster structure (64). These concepts, if they can be extended to other systems, offer the possibility of using clusters to accomplish unique synthetic chemistry and to form various classes of superatoms that would be analogues to elements of the periodic table.…”
Section: Clusters In Materials Sciencementioning
confidence: 92%
“…Because Al 13 Ϫ has 40 valence electrons, its inertness could be understood in terms of a closed electronic shell, as could the 23-and 37-atom-containing systems, which also have closed electronic configurations (62). These and other observations began to suggest that the jellium picture, although extremely simplistic and marked by indisputable limitations, is amazingly successful in describing many of the global observed electronic features in a variety of systems and that certain metallic clusters could be described as superatoms (63,64). The prospect of using clusters as building blocks thereby arose.…”
Section: Clusters In Materials Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…It is attractive in its simplicity, though also rather restricted in the class of clusters to which it can be straightforwardly applied (Kuznetsov et al 2002). The idea is that MOs in clusters can be viewed as analogs of AOs in atoms, and clusters themselves can be viewed as mimics of elements in the periodic table in their chemical behavior (Bergeron et al 2005;Castleman 22 and Khanna 2009;Clayborne et al 2011;Jena 1992, 1995;). History began with the milestone discovery of a shell structure in the electronic spectra of small nanoclusters of monovalent alkali atoms such as Na and K (~10 2 or fewer delocalized electrons) by Walter Knight and co-workers (Knight et al 1984).…”
Section: Super-atom Model Is a Specific Way Of Viewing And Rationalizmentioning
confidence: 99%